2019
DOI: 10.1139/cjce-2017-0679
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters affecting horizontal cracking in continuously reinforced concrete pavement (CRCP)

Abstract: Field evaluation of distresses in continuously reinforced concrete pavement (CRCP) indicated punch-out distress associated with horizontal cracking at the depth of the longitudinal steel is the most severe performance problem in CRCP. The developed 3-D model was used to perform a parametric analysis to determine the effects of critical loading location, concrete properties, and longitudinal steel design on horizontal cracking potential. The maximum vertical tensile stresses in the concrete were slightly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Therefore, a rational increase in the BFRP diameter is an effective way to reduce the crack spacing and width of the CRCP with BFRP bars. With the aforementioned range of BFRP spacing (6,8,10,12, and 14 cm) and BFRP diameter (10,12,14,16, and 18 mm), the reinforcement content for each combination of spacing and diameter can be calculated within the range of 0.22% to 1.63%. The relationship between the reinforcement content of BFRP and the crack spacing and width are presented in Figure 10.…”
Section: Reinforcement Content Of Bfrpmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a rational increase in the BFRP diameter is an effective way to reduce the crack spacing and width of the CRCP with BFRP bars. With the aforementioned range of BFRP spacing (6,8,10,12, and 14 cm) and BFRP diameter (10,12,14,16, and 18 mm), the reinforcement content for each combination of spacing and diameter can be calculated within the range of 0.22% to 1.63%. The relationship between the reinforcement content of BFRP and the crack spacing and width are presented in Figure 10.…”
Section: Reinforcement Content Of Bfrpmentioning
confidence: 99%
“…However, the corrosive property of steel can significantly reduce the bond stiffness of the steel and concrete, causing a decrease in the load transfer efficiency and aggregate interlock between the adjacent concrete slabs, therefore widening the crack width, which is an important indicator for CRCP performance [1,2]. There have been many studies evaluating the crack behavior and structural performance of CRCP [3][4][5][6][7][8][9], indicating that the aggregate type, the reinforcement content and depth, the slab-base friction, and the environmental load, etc., have great effect on the crack spacing and crack width and, as a result, affect the structural performance of the CRCP.…”
Section: Introductionmentioning
confidence: 99%
“…CRCP behaves symmetrically with respect to the center of the two consecutive transverse cracks and the pavement lane under environmental loading [26][27][28][29]. Therefore, one-half of the concrete slab on either side of saw-cuts and another half of the pavement lane are taken into account by considering the appropriate boundary conditions.…”
Section: Geometry Configuration Of the Crcp Segmentmentioning
confidence: 99%
“…Being closer to the outer concrete slab face as per boundary conditions, the tips of shorter saw-cut experiences larger crack strains than those of conventional and longer saw-cut. Crack strain Time (Days) L=200 mm L=400 mm L=600 mm Previous studies on the fatal distress in CRCP showed that most of the punch-out distress occurs in the outer lane of pavement slab [12,18,27,29,38,39,45,46]. It has also been reported that the randomness (the presence of closely spaced and divided cracks) in the transverse crack pattern increases the potential risk of punch-outs development in CRCPs [11,12,16,47,48].…”
Section: Effect Of Saw-cut Length On Early-age Crack Inductionmentioning
confidence: 99%
“…Previous field studies indicated that punch-out is the most severe structural distress in CRCPs [3][4][5][6][7][8]. During the mid-1980s,Texas Department of Transportation addressed this distress by modifying the design and construction practices.…”
Section: Introductionmentioning
confidence: 99%